Search for Higgs boson pair production in the bb¯bb¯ final state from pp collisions at s√=8 TeVwith the ATLAS detector - Aad, G. (2015)
A search for Higgs boson pair production pp→hh is performed with 19.5 fb−1 of proton?proton collision data at s√=8 TeV, which were recorded by the ATLAS detector at the Large Hadron Collider in 2012. The decay products of each Higgs boson are reconstructed as a high-momentum bb¯ system with either a pair of small-radius jets or a single large-radius jet, the latter exploiting jet substructure techniques and associated b-tagged track-jets. No evidence for resonant or non-resonant Higgs boson pair production is observed. The data are interpreted in the context of the Randall?Sundrum model with a warped extra dimension as well as the two-Higgs-doublet model. An upper limit on the cross-section for pp→G∗KK→hh→bb¯bb¯ of 3.2 (2.3) fb is set for a Kaluza?Klein graviton G∗KK mass of 1.0 (1.5) TeV, at the 95 % confidence level. The search for non-resonant Standard Model hh production sets an observed 95 % confidence level upper limit on the production cross-section σ(pp→hh→bb¯bb¯) of 202 fb, compared to a Standard Model prediction of σ(pp→hh→bb¯bb¯)=3.6±0.5 fb.